A rational approach to the regioselective deacetylation of 2′,3′,5′-tri-O-acetyluridine by Novozym 435 catalysed alcoholysis - Gudiño, Esteban Dario; Iglesias, Luis Emilio; Ferreira, María Luján (Biochimica et Biophysica Acta (BBA) - Proteins and Proteomics)
To give a rational explanation for the behaviour of 2′,3′,5′-tri-O-acetyluridine (TAU) catalysed alcoholysis using Novozym 435, the commercial biocatalyst with immobilized Candida antarctica lipase B (CALB), a set of experiments analyzing the role of the alcohol/substrate (A/S) molar ratio, alcohol/biocatalyst (A/B) and substrate/biocatalyst (S/B) mass ratios were carried out. At a A/S = 120 and a S/B = 6.16, 2′,3′-di-O-acetyluridine (DAU) was obtained in 92% at 22 h. The observed trend towards the exclusive formation of DAU at very high alcohol amounts can be explained on the basis of the change of substrate orientation from normal to inverse. The simple molecular modelling analysis supports that key O/H atoms from TAU and the resulting intermediates display the adequate distances to generate productive binding only when the inverse coordination of TAU is present through the 5′-moiety of TAU, at high ethanol concentrations. At these conditions a possible allosteric-like effect of ethanol, combined with water in an H-network in the catalytic triad and in its neighbourhood, could explain the high selectivity towards the production of DAU at selected conditions. Fil: Gudiño, Esteban Dario. Universidad Nacional de Quilmes; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Iglesias, Luis Emilio. Universidad Nacional de Quilmes; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Ferreira, María Luján. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Planta Piloto de Ingeniería Química. Universidad Nacional del Sur. Planta Piloto de Ingeniería Química; Argentina